Enhancing Chinese students’ academic engagement: the effect of teacher support and teacher–student rapport - Pan, Xiaoquan; Yao, Yuanyuan (Frontiers in Psychology, 2023)
Academic engagement plays an undeniable role in students’ leaning outcome. Therefore, identifying the influential antecedents of promoting students’ academic engagement is extremely crucial. Despite previous empirical studies have delved into the part played by several student-related and teacher-related factors in triggering Chinese students’ academic engagement, the exploration on the roles of teacher support and teacher–student rapport is still scant. Thus, this study attempts to concentrate on the influence of teacher support and teacher–student rapport on undergraduate students’ academic engagement in China. Three scales of the questionnaire—one each for teacher’s support, student-teacher rapport, and the level of academic engagement—were completed by a total of 298 undergraduate students. Spearman Rho test was adopted to detect the correlations between the variables. Following that, multiple regression analysis was used to estimate the predictive power of the dependent variables. The result found that teacher support and teacher–student rapport exert a tremendous influence on boosting Chinese students’ academic engagement. The leading implications and future directions are also presented.